Repeatability and Reproducibility of Retinal Neuronal and Axonal Measures on Spectral-Domain Optical Coherence Tomography in Patients with Cognitive Impairment - Loh, Edwin Hong-Teck; Ong, Yi-Ting; Venketasubramanian, Narayanaswamy; Hilal, Saima; Thet, Naing; Wong, Tien Yin; Chen, Christopher P. L.; Cheung, Carol Yim-lui (Frontiers in Neurology, 2017)
(Keywords: Retina, Reproducibility, Repeatability, Mild Cognitive Impairment, Dementia, Optical Coherence Tomography) Background: With increasing interest in determining if measurement of retinal neuronal structure with spectral-domain optical coherence tomography (SD-OCT) is useful in accessing neurodegenerative process in cognitive decline and development of dementia, it is important to evaluate whether the SD-OCT measurements are repeatable and reproducible in patients with Alzheimer’s disease (AD) or mild cognitive impairment (MCI). Methods: This is a retrospective cohort study. Patients with AD or MCI with no change in global clinical dementia rating (CDR) score at 1-year follow-up were eligible to be included. (GC-IPL) Macular ganglion-cell inner plexiform layer (GC-IPL) and peripapillary retinal nerve fiver layer (RNFL) thicknesses were measured with a SD-OCT (Cirrus HD-OCT, Carl Zeiss Meditec, Dublin, CA) at baseline, 6-month and 1-year follow-up visits. At baseline, SD-OCT scans were repeated to access intra-visit repeatability of the SD-OCT measurement. SD-OCT measurement over three visits were used to access inter-visit reproducibility. We calculated intra-class coefficients (ICC) and coefficients of variation (CoV). Results: We included 32 patients with stable AD and 29 patients with stable MCI in the final analysis. For GC-IPL measures, the average intra-visit ICC was 0.969 (range: 0.948-0.985) and CoV was 1.81% (range: 1.14-2.40%); while the average inter-visit ICC was 0.968 (range: 0.941-0.985) and CoV was 1.91% (range: 1.24-2.32%). The average ICC and CoV of intra-visit RNFL measured was 0.965 (range: 0.937-0.986) and 2.32% (range: 1.34-2.90%). The average ICC and CoV of inter-visit RNFL measures was 0.927 (range: 0.845-0.961) and 3.83% (range: 2.71-5.25%). Conclusions: Both GC-IPL and RNFL thickness measurements had good intra-visit repeatability and inter-visit reproducibility over 1 year in elderly patients with stable AD and MCI, suggesting that SD-OCT is a reliable tool to assess neurodegenerative process over time.